1995
DOI: 10.1097/00000539-199509000-00031
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effects of Methohexital, Propofol, and Etomidate for Electroconvulsive Therapy

Abstract: The intravenous anesthetics which are commonly used for electroconvulsive therapy (ECT) possess dose-dependent anticonvulsant properties. Since the clinical efficacy of ECT depends on the induction of a seizure of adequate duration, it is important to determine the optimal dose of the hypnotic for use during ECT. We compared the duration of seizure activity and cognitive recovery profiles after different doses of methohexital, propofol, and etomidate administered to induce hypnosis prior to ECT. Ten outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 20 publications
7
110
1
5
Order By: Relevance
“…However, Avramov et al [18] discovered that the rates of cognitive recovery were similar when propofol was compared with methohexital and etomidate, which indicated controversy as to the possible benefits of propofol. Based on etomidate anesthesia in ECT, it was found that additional propofol (0.5 mg/kg) prevented the cognitive decrements induced by ECT [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, Avramov et al [18] discovered that the rates of cognitive recovery were similar when propofol was compared with methohexital and etomidate, which indicated controversy as to the possible benefits of propofol. Based on etomidate anesthesia in ECT, it was found that additional propofol (0.5 mg/kg) prevented the cognitive decrements induced by ECT [19].…”
Section: Discussionmentioning
confidence: 99%
“…Etomidat (0,15-0,3 mg/kgKG) führt im Vergleich zu Methohexital, Thiopental und Propofol zu einer längeren Krampfdauer und bietet sich daher als Alternative bei Patienten an, bei denen die Krampfdauer trotz maximaler elektrischer Stimulation unter Anwendung dieser Hypnotika zu kurz war [5,54] …”
Section: Etomidatunclassified
“…Propofol scheint einen stärkeren antikonvulsiven Effekt als die vorgenannten Anäs-thetika zu haben; hierbei lässt sich auch hier wieder ein dosisabhängiger Effekt nachweisen [5,22,27]. So war die Krampfdauer nach niedrigen Dosierungen von 0,75 mg/kgKG in etwa mit derjenigen nach einer Standarddosis von Methohexital vergleichbar, während sie nach hö-heren Dosierungen von 1,0-1,5 mg/kgKG signifikant kürzer war als nach Methohexital, Thiopental oder Etomidat.…”
Section: Propofolunclassified
See 1 more Smart Citation
“…Entsprechend den Untersuchungen von Avramov und White hat Propofol sogar profunde antikonvulsive Wirkungen [5]. So hat sich das Medikament im Anästhesiebereich insgesamt als sehr sicher erwiesen.…”
Section: Wie Hat Sich Propofol Bewährt?unclassified